Need for a Strong FOPL in India-position Statement - Nandita Sharma; Yogesh Bahurupi; Suneela Garg; Umesh Kapil; Pankaj Bhardwaj; Om Prakash Bera; Mahendra Singh; Pradeep Aggarwal (Indian Journal of Community Medicine)
Due to lifestyle changes, urbanization, and the rise of ultra-processed foods (UPF), India is undergoing a rapid nutritional transformation. These dietary shifts have significantly contributed to the rise in non-communicable diseases (NCDs), which now account for a substantial portion of mortality and disease burden in the country. A strong Front-of-Pack Labeling (FOPL) system is recommended in this position statement as a powerful public health tool to address this issue. Through the provision of easily comprehensible nutritional data, FOPL encourages food producers to create healthier goods while empowering customers to make educated dietary decisions. Current labeling practices in India, such as the Indian Nutritional Rating (INR), fall short due to complexity and voluntary implementation. This paper evaluates international best practices, including warning labels and color-coded systems, highlighting their effectiveness in reducing the consumption of high-risk foods. We argue for straightforward, uniform, and globally evidence-based approach to mandatory FOPL implementation. Policymakers, industry stakeholders, and public health advocates must collaborate to develop an FOPL system that addresses India’s unique dietary landscape. Such an initiative is crucial to reducing the NCD burden and fostering healthier eating habits nationwide.